ISLAMIC JURISDICTION SYSTEM IN SAUDI ARABIC - Rosadi, Aden (Al-Ahwal Al-Syakhsiyyah: Jurnal Hukum Keluarga dan Peradilan Islam, 2021)
This paper will discuss the Islamic justice system in the country of Saudi Arabia. Through a normative juridical approach it can be described that Saudi Arabia is an Islamic country that is consistent in implementing criminal law. In contrast to the continental legal system and the anglo saxon which are guided by the policies of the Government, Parliament and the judiciary. In addition, in practice, Islamic criminal law is also guided by the opinion of the school, both the official school, namely the hambali school or other schools. Thus it can be concluded that the judiciary bodies in Arab countries are entirely guided by Islamic law, because Islamic law is the positive law. On the other hand, it also does not codify the law because it can narrow the space for ijtihad to move and the sources of legal making, but this in turn can lead to different judges' decisions. For this reason, there is Majlis al-A'la li al-Qadha (Supreme Court of Justice) to oversee the decisions of the court judges under their ranks. In addition, the hierarchy of judicial bodies in the Arab country consists of three levels, namely the High Court as the Supreme Court, the Court of Appeal and the Court of First instance.